Correlation between Nutrition Status and Fitness among Ele-mentary School Students in Bali Province - Cakrawati, Cok Istri Dewiyani (WMJ (Warmadewa Medical Journal), 2020)
Lack of physical activity and excess energy consumption have an impact on increasing the prevalence of obesi-ty in elementary school children. Furthermore, this condition is often associated with cardiorespiratory fitness. This condition certainly has an impact on increasing the risk of non-communicable diseases. It is necessary to know the nutritional status and physical fitness level in elementary school children so that early intervention can be done to prevent obesity among children. This study uses a cross-sectional study design. The population in this study were elementary school students aged 10-12 years in Bali Province. A total of 704 students were selected by purposive sampling. Data collected included the characteristics of respondents through interview methods, anthropometry measurements (BMI/Age), and fitness measurements. Fitness Tests are carried out using the single test method (a walk/run test as far as 1200 meters). Eligibility criteria are students aged 10-12 years, not in illness/disability, and willing to take a fitness test. Data were analyzed descriptively and analyti-cally using the chi-square method. This study found that nutritional status for very thin, thin, normal, over-weight, and obese were 3.6%, 19.5%, 46.1%, 29.6%, and 1.2%, respectively. Meanwhile fitness for less fit, quite fit and fit respectively were 64.1%, 22.7%, and 13.15%, respectively. There is a significant relationship obtained between age, sex, and nutritional status with fitness (p <0.05). It is recommended to improve the nu-tritional status of overweight and obese students as well as increase physical activity among students to im-prove their fitness.